Chemical and Biologically Active Constituents of Schisandra sphenanthera Rehd. et. - Du, Jing-Ling; Zou, Xiao-Hua; Zhao, Fei; Jin, Yong-Sheng; Tuo, Xi-Ping; Chen, Hai-Sheng (Asian Journal of Chemistry, 2012)
Twenty-two known constituents were isolated from Schisandra sphenanthera Rehd.et. and their structures were elucidated on the basis of chemical reaction and spectral analysis. Six compounds of them were isolated from this plant for the first time. Among these isolated compounds, schisandrone (SCB-11) showed significant effects on alzheimer disease (AD).